A virus‐derived microRNA targets immune response genes during SARS‐CoV‐2 infection. (16th December 2021) - Singh, Meetali; Chazal, Maxime; Quarato, Piergiuseppe; Bourdon, Loan; Malabat, Christophe; Vallet, Thomas; Vignuzzi, Marco; van der Werf, Sylvie; Behillil, Sylvie; Donati, Flora; Sauvonnet, Nathalie; Nigro, Giulia; et al.
Abstract: SARS‐CoV‐2 infection results in impaired interferon response in patients with severe COVID‐19. However, how SARS‐CoV‐2 interferes with host immune responses is incompletely understood. Here, we sequence small RNAs from SARS‐CoV‐2‐infected human cells and identify a microRNA (miRNA) derived from a recently evolved region of the viral genome. We show that the virus‐derived miRNA produces two miRNA isoforms in infected cells by the enzyme Dicer, which are loaded into Argonaute proteins. Moreover, the predominant miRNA isoform targets the 3′UTR of interferon‐stimulated genes and represses their expression in a miRNA‐like fashion. Finally, the two viral miRNA isoforms were detected in nasopharyngeal swabs from COVID‐19 patients. We propose that SARS‐CoV‐2 can potentially employ a virus‐derived miRNA to hijack the host miRNA machinery, which could help to evade the interferon‐mediated immune response. Synopsis: SARS‐CoV‐2 produces two miRNAs derived from a conserved stem‐loop structure of the ORF‐7a transcript in a Dicer‐dependent manner. These virus‐derived miRNAs interact with host Argonaute and can repress host innate immune response genes in cultured cells. CoV2‐miR‐O7a.1 and CoV2‐miR‐O7a.2 are generated from the SARS‐CoV‐2 genome by a Dicer‐dependent cleavage of a stem‐loop structure of ORF7a. The stem‐loop structure is under selective pressure and is conserved in various SARS‐CoV‐2 variants but not in SARS‐CoV. CoV2‐miR‐O7a.2 can target 3′UTRs of interferon‐stimulated genes and represses their expression in a miRNA‐like fashion. CoV2‐miR‐O7a.1 and CoV2‐miR‐O7a.2 are both detected in nasopharyngeal swabs from COVID‐19 patients. Abstract : SARS‐CoV‐2 produces two miRNAs derived from a conserved stem‐loop structure of the ORF‐7a transcript in a Dicer‐dependent manner. These virus‐derived miRNAs interact with host Argonaute and can repress host innate immune response genes in cultured cells.